Do stressful life events impact long-term well-being? Annual change in well-being following different life events compared to matched controls - Howard, Chloe; Overall, Nickola C.; Sibley, Chris G. (Frontiers in Psychology, 2022)
Available longitudinal evidence suggests that personal growth following adversity may not be as prevalent as suggested in cross-sectional research. Firm conclusions regarding resiliency versus post-traumatic growth following adverse events are further tempered by the restricted range of outcomes assessed when examining resilience, the focus on specific adverse events or cumulative adversity scores that hinder comparisons between event types, and the relative scarcity of analyses including matched control groups. The current study addresses these gaps by leveraging longitudinal panel data comparing annual change in well-being from 2018 to 2019 for people who experienced a major life stressor relative to propensity score matched controls who did not experience such stressors over the same period. Moreover, independent comparisons are conducted across three distinct event categories: traumatic interpersonal events (Nmatched pairs = 1,030), job loss (Nmatched pairs = 1,361), and birth (Nmatched pairs = 1,225), and five self-reported well-being indicators: life satisfaction, felt belongingness, self-esteem, meaning in life, and gratitude. Results indicate that people’s well-being (across all five indicators) remained consistent over the year in independent analyses of samples experiencing each of the three types of events, and did not differ from matched controls. These findings indicate high population levels of psychological resilience, in the sense that people did not decrease in annual well-being following various life events. These findings also fail to detect significant evidence for possible post-traumatic growth, insofar as such growth might relate to a broad range of different aspects of well-being.